Pengaruh Game Super Sus Terhadap Pemerolehan Aspek Sintaksis Pada Anak Usia 9 Tahun - Amalia, Marisa Nurril; Putra, Dona Aji Karunia (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this journal article research is to describe the forms of acquisition of syntactic aspects due to online games in children aged 9 years. his study used descriptive qualitative method. The subject in this study was a 9 year old child named Bima. The data in this study is in the form of qualitative data. The data collection for this research was carried out using notetaking techniques, interviewing 9-year-old children in their home environment who play online games. The results of the study show that the child is able to say declarative, imperative and interactive sentences.